Diversity variability of native corn cobs in the high zone of Totonacapan, mesoamerica - Alemán-Chávez, Isabel; Rivera-Fernández, Andrés; Lara-Capistrán, Liliana; Ledea-Rodríguez, José (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2024)
Mexico is considered one of the origins of corn (Zea mays L.), and in the Totonacapan area there are still native plant genetic resources that have not been characterized and are under threat by the introduction of improved genetic material and/or commercial seeds in traditional production systems. It was evaluatedthe morphological variability of native corn in the municipalities of Coahuitlán, Mecatlán and Filomeno Mata from the Totonacapan region. The experimental design implemented was non-balanced hierarchical, and principal component and correspondence analysis were also developed; six producers were visited per community within each municipality. The corn from Filomeno Mata was characterized by thick cobs, long leaves (totomoxtle) and large ears, while those from Coahuitlán and Mecatlán converge in heavy cobs with many long and heavy grains per row. The characteristics of the municipalities define the agricultural practices of the producers. Finally, significant differences (P ≤ 0.001) were found in the length, perimeter and coverage of the leaf, cob, and grain between producers from different municipalities and from the same municipality. The morphological diversity of native corn between producers from different communities is fostered by differences in the productive practices they employ within each municipality.